Analisis kinerja keuangan pt sumber alfaria trijaya tbk sebagai dasar pengambilan keputusan investasi yang minim risiko - Husnia, Nidaul (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the feasibility of investment as a basis for investment decision making in PT Sumber Alfaria Trijaya Tbk (Alfamart) through a fundamental analysis approach, by considering financial ratios such as Book Value Per Share (BVPS), Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Dividend Payout Ratio (DPR). The results of the study indicate that Alfamart has a relatively stable and prospective financial performance, supported by significant BVPS growth and a fairly good profitability ratio. The decline in DPR indicates the company’s strategy of prioritizing business expansion to support long-term growth. In addition to potential profits, this study also identifies various investment risks that investors need to consider, including market risk, interest rate risk, inflation risk, exchange rate risk, business risk, financial risk, liquidity risk, and country risk. This study recommends a portfolio diversification strategy to mitigate total investment risk, so that investors can obtain optimal returns with more controlled risks. Thus, investment in PT Sumber Alfaria Trijaya Tbk shares is considered feasible, as long as investors continue to implement effective risk management.